PROMOSI OBJEK WISATA ALAM PERTAMINA LIRIK DI KABUPATEN INDRAGIRI HULU PROVINSI RIAU - Latifah, Lu'lu'atul; ,, Etika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
Indragiri Hulu Regency, Riau Province, is a region with significant potential for tourism development, particularly natural tourism. One such destination is the Pertamina Lirik Nature Tourism Object, located in Lirik District. Despite its natural resources and relatively adequate facilities, this attraction has not been able to attract optimal tourist visits. One of the main factors influencing this situation is limited funding and human resources for promotional activities. This study aims to determine how the management of the Pertamina Lirik Nature Tourism Object promotes itself, as well as to identify the supporting and inhibiting factors in its implementation. The research method used was qualitative with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation, referring to the five promotional tools according to Kotler and Armstrong (2017). The results showed that the management had implemented four of the five promotional tools. Advertising focused on Instagram, Facebook, and local radio. Sales promotions were carried out by holding various competitions and offering ticket discounts on Sundays. Publicity was provided through local mass media coverage of the activities. Direct marketing relied on word-of-mouth promotion from visitors. Individual sales have not been successful. Supporting promotional factors include a strategic location along the Trans-Sumatra Highway, social media sharing and hashtags, and programs supported by CSR and educational activities. Meanwhile, inhibiting factors include a lack of active management members, insufficient funding, and limited professional human resources in the tourism sector. With proper promotion, the Pertamina Lirik Nature Tourism Object has the potential to become a stable, leading tourist destination. Keywords: Tourism, Promotion, Tourist Attractions, Supporters and Inhibitors